(untitled) (Sinología hispánica. China Studies Review, 2021)
By the end of the 16th century and at the beginning of the 17th century, the Spanish Dominicans initiated their missions with the Chinese merchants in Philippine Islands. This is a preparing period before they land on the Continental China. During these years, they published fore incunabulae in Chinese: Testimony of the True Religion (Bian Zhengjiao Zhenchuan Shilu, Juan Cobo, 1593), Christine Doctrine (Dominican Friars, 1604?), Memorial of the Christian Life in Chinese (Liaoshi Zhengjiao Bianlan, Domingo de Nieva, 1606), Symbol of Faith in Chinese (Gewu Qiongli Bianlan, Thomas mayor, 1607). This article will discuss how the Dominican missionaries translated the western terms in these incunabulae, the coherence in the use of translated terms between different incunabulae, the types of terms concerned in them and the difficult situation the friars faced translating them. Through this investigation, the early Dominican evangelic policy and method towards the local Chinese in Philippines will be revealed. Also we will comment on the particular methodology of the translation of cultural references between Western languages and Chinese.